(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reviews the main semantics provided by the category of negation, discusses the ways of expressing the negation a sentence. The article also compares the ways of expressing negation within Uzbek and English sentences which shows differences in the linguistic world pictures.